Effects of four types of chinese medicines as concomitant drugs with azithromycin for the treatment of mycoplasma pneumonia in children in China: a network meta-analysis - Jin,Lairun (2021)
SUMMARY OBJECTIVE: The purpose of this study was to evaluate the efficacy of the use of four concomitant Chinese medicines with azithromycin in the treatment of mycoplasma pneumonia in children (MPC) by using network meta-analysis (NMA) and ranking them according to their performances. METHODS: There were a total of 130 randomly controlled trials of four different concomitant Chinese medicines with azithromycin for the treatment of MPC in many databases, and an NMA was conducted in them by using Stata (version 13.0) software to evaluate the odds ratio (OR) and sequence of the different combinations. The included studies were divided into two groups: control group (azithromycin alone) and observation group (one of four azithromycin combinations). RESULTS: A total of 13119 cases were included in this study, and the results showed that the pooled OR and 95% confidence interval (CI) of MPC improvement compared with azithromycin alone were 4.76 (3.18–7.14) for azithromycin and Reduning, 5.66 (4.50–7.12) for azithromycin and Tanreqing, 4.84 (3.35–7.01) for azithromycin and Xiyanping, and 4.58 (3.59–5.83) for azithromycin and Yanhuning, respectively. This study shows the significant efficacy of Chinese concomitant drug. The combination of azithromycin with Tanreqing is the best candidate of concomitant drug in terms of clinical efficacy. Its surface under the cumulative ranking (SUCRA) score was 85.5, while the SUCRA score for the azithromycin and Yanhuning combination was the worst, which is 48.4. CONCLUSIONS: The combination of azithromycin with Tanreqing is the most promising group among four combinations for the treatment of MPC.